Interaction analysis on social-education of Indonesian school students: A literacy activity - Rafid, Rahmad; Khotimah, Farizal Khusnul (Goodwood Publishing, 2021)
Purpose: The purpose of this study is to analyze the socio-educational interactions between teachers and students. This article also looks at a literacy activity utilized by the teachers and students and their interaction patterns. Research methodology: This research applied a naturalistic approach and descriptive qualitative research design. The data were collected through observation, interviews, and documentation. The data then were analyzed descriptively using the Miles and Huberman analysis model, namely data condensation, data presentation, and concluding. Results: The research results show that to improve student literacy, there were two patterns of interaction: first, a one-way interaction pattern centered on the teacher as a facilitator, corrector, evaluator in literacy activities: second, a multi-directional interaction pattern occurred. Literacy activities aim to train the learners’ ability in reading, understanding and commenting. During the core activities, several aspects of the interactions occur between teachers and students, such as conveying information, explaining, motivating, and proposing to students. At the closing stage of literacy, several aspects of the interaction between teachers and students occur. Making summaries and reading about the literacy activities have provided directions for further literacy activities and conducting evaluations that have been carried out. Limitations: There are limitations to the researcher, so this research is limited to one school only with the object of research on all students and teachers assigned to literacy activities at SMA Negeri 1 Latambaga. Contribution: The study is expected to assist the schools in monitoring the literacy activities and developing student literacy, whereas, for students, this study is expected to improve their literacy and broaden their insights about technological and scientific developments.